2022
DOI: 10.1101/2022.08.02.502461
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Omicron BA.2 breakthrough infection enhances cross-neutralization of BA.2.12.1 and BA.4/BA.5

Abstract: Recently, we reported that BNT162b2-vaccinated individuals after Omicron BA.1 breakthrough infection have strong serum neutralizing activity against Omicron BA.1, BA.2, and previous SARS-CoV-2 variants of concern (VOCs), yet less against the highly contagious Omicron sublineages BA.4 and BA.5 that have displaced previous variants. As the latter sublineages are derived from Omicron BA.2, we characterized serum neutralizing activity of COVID-19 mRNA vaccine triple-immunized individuals who experienced BA.2 break… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 36 publications
3
33
1
Order By: Relevance
“…5g). More NTD mutations does not contribute to stronger evasion in BA.2.75-based mutants, but we observed significant reduction in NT50 of BA.2/BA.5 convalescents against BA.5-based mutants with K147E+W152R, suggesting BA.2/BA.5 convalescent plasma contains large proportion of NTD-targeting antibodies 43 . As the NTD of BA.1 is quite different from that of BA.2 and BA.5, we did not observe significant effects of NTD mutations on the efficacy of BA.1 convalescent plasma.…”
Section: Convergent Evolution Could Eventually Nullify Plasma Neutral...contrasting
confidence: 50%
See 1 more Smart Citation
“…5g). More NTD mutations does not contribute to stronger evasion in BA.2.75-based mutants, but we observed significant reduction in NT50 of BA.2/BA.5 convalescents against BA.5-based mutants with K147E+W152R, suggesting BA.2/BA.5 convalescent plasma contains large proportion of NTD-targeting antibodies 43 . As the NTD of BA.1 is quite different from that of BA.2 and BA.5, we did not observe significant effects of NTD mutations on the efficacy of BA.1 convalescent plasma.…”
Section: Convergent Evolution Could Eventually Nullify Plasma Neutral...contrasting
confidence: 50%
“…We then evaluated the potency of NTD-targeting NAbs against BA.2.75, BA.5 and BA.2 with selected NTD mutations using a panel of 14 mAbs, as it is reported that NTD-targeting antibodies are abundant in plasma from BA.2 breakthrough infection 43 . The selected mutations are most from BA.2.75, except for R237T which was designed to escape mAbs targeting a certain epitope reported recently 20 .…”
Section: Convergent Evolution Could Eventually Nullify Plasma Neutral...mentioning
confidence: 99%
“…Sera were obtained from a non-interventional study researching vaccinated patients that had experienced Omicron breakthrough infection, and from the biosample collections of BNT162b2 vaccine trials. Data for the reference cohorts were previously published and are used here for benchmarking ( 17, 21 ).…”
Section: Resultsmentioning
confidence: 99%
“…Serum neutralizing activity was tested in a well-characterized pseudovirus neutralization test (pVNT) ( 21, 25, 26 ) by determining 50% pseudovirus neutralization (pVN 50 ) geometric mean titers (GMTs) with pseudoviruses bearing the S glycoproteins of the SARS-CoV-2 wild-type strain or Omicron BA.1, BA.2, and the BA.2-derived sublineages BA.2.12.1, and BA.4/BA.5 (BA.4 and BA.5 are identical in their S glycoprotein sequence). In addition, we assayed SARS-CoV (herein referred to as SARS-CoV-1) to detect potential pan-Sarbecovirus neutralizing activity ( 27 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation